Robotics, automation, and control in industrial and service settings - Luo, Zongwei, 1971- (Advances in civil and industrial engineering (ACIE) book series., 2015)
"This book meets the challenges presented by the rise of ubiquitous computing by providing a detailed discussion of best practices and future developments in the field of automation and robotics"--